Aplicación de un sistema de costos predeterminados en la elaboración de las prendas Jean y Camisa en el Centro de Formación Providencia (2023)
The degree work focused on the application of a system of predetermined costs in the production of clothing, specifically in the production of jeans and shirts, at the Providencia Training Center located in Palmira, Valle del Cauca.